PERAN KOMUNITAS TANGAN DI ATAS (TDA) KOTA SAMARINDA TERHADAP PENGEMBANGAN KEWIRAUSAHAAN PEMUDA DI KOTA SAMARINDA - Iqbal Saputra Zana (Jurnal Paradigma (JP), 2021)
This article aims to determine the Tangan di Atas (TDA) community in Samarinda City in the development of youth entrepreneurship in Kota Samarinda. This article's focus discusses entrepreneurship training, providing guidance, promotion of products or services, assistance to access capital by TDA, and inhibiting factors and supporting factors. Using a qualitative approach and interactive model data analysis techniques, the research findings show that the Hand on Above (TDA) community in Samarinda City has carried out entrepreneurship training activities and provided mentoring through business mentoring classes to youth entrepreneurs members of TDA Samarinda. The TDA Samarinda community also facilitates the promotion of products or services through regional entrepreneurial parties and assistance to access capital through the Meet The Investor (MTI) program.Keywords: role, TDA Community, entrepreneurship, youth